Seismic Performance of Pile Slab Bridges with Variations in the Number of Lateral Pile Configurations - Alex Kurniawandy; F. R. Sihombing; Ismeddiyanto (Civil Engineering Journal, 2026)
This study aims to evaluate the seismic performance of pile slab bridge structures in Riau Province as a mitigation measure against the high rate of bridge damage reported by Bina Marga in 2023, totaling 366 bridges with varying levels of deterioration. The analysis was conducted using the nonlinear static pushover method on three pile slab bridge models with five, six, and seven pile configurations to assess the influence of pile quantity on structural capacity. Structural modeling and analysis were performed using finite element–based software to obtain capacity curves, lateral displacements, and performance points in both X and Y directions. The results show that increasing the number of piles from five to seven enhances base shear capacity by up to 12% in the X-direction and 14% in the Y-direction, while lateral displacement and drift ratio increase by 7% and 9%, respectively. However, the five-pile model reached a plastic state at the performance point, with plastic hinges remaining within the Operational–Life Safety limit, indicating safe deformability under seismic loads. This research contributes a comparative evaluation of lateral pile configurations in pile slab bridge seismic performance, which has not previously been analyzed in the case of bridges in Riau Province.